(untitled) (Global Journal of Computer Science and Technology, 2023)
An operating system serves as a fundamental component of any computer system Scheduling lies at the core of operating system functionality involving the arrangement of processes to execute in a well-defined manner The primary goal of scheduling is to enhance system efficiency and speed Several fundamental scheduling algorithms exist including First Come First Serve FCFS Round Robin Priority-Based Scheduling and Shortest Job First SJF This thesis primarily focuses on the Round Robin Scheduling algorithm and seeks to address certain limitations associated with it One notable drawback of Round Robin Scheduling is the critical choice of the time quantum If the time quantum is excessively large the scheduling behavior closely resembles that of FCFS Conversely a smaller time quantum leads to a higher number of context switches The central objective here is to overcome this limitation inherent to the traditional Round Robin scheduling algorithm thereby maximizing CPU utilization and enhancing system efficiency In this thesis we propose an innovative algorithm that classifies processes into two categories high-priority processes and low-priority processes This novel scheme significantly reduces the average waiting time of high-priority processes regardless of the presence of low-priority processes The overall average waiting time varies based on the specific set of processes under consideration Our analysis demonstrates that the proposed scheme consistently outperforms previously suggested methods resulting in reduced average waiting times for the selected process sets